A physics-based model for frost buildup under turbulent flow using direct numerical simulations. (January 2022) - Zgheib, N.; Farzaneh, M.; Balachandar, S.; Sherif, S.A.
Highlights: Direct numerical simulation model for frost buildup under turbulent flow. Frost builds up at a much faster rate when overlying flow is turbulent. A densification model is proposed to address varying frost properties. Frost shows a streaky nature as it builds up under turbulent flow. Frost thickness and surface properties can vary substantially under turbulent flow. Abstract: We present a new model for frost buildup under turbulent (and laminar) flow using direct numerical simulations. The physical model consists of two layers, the air and the frost. The air layer is fully resolved and consists of solving for the velocity, temperature, and vapor mass fraction fields. The frost layer thickness is resolved using conservation of mass and energy. Both phases are dynamically coupled using the immersed boundary method. Three-dimensional simulations are conducted in an open-channel configuration. A number of challenges need to be overcome to make these simulations feasible. First, to enforce far-field conditions of zero gradient and prescribed mean temperature and humidity, a source term is added to the energy and transport equations in the flow solver. Second, the mean frost thickness is subtracted after each time step to ensure a constant mean flow thickness and level of turbulence in the numerical domain. Third, a slow-time acceleration approach, which accelerates the frost buildup by a predetermined factor, is employed to bridge the gap between the fast turbulent and slow frost buildup time scales. Finally, a frost densification scheme is used to overcome the difficulties of vertically varying frost properties. The model is validated by comparing the frost thickness and frost thickness buildup rate over a period of one hour from a cooled flat plate experiment. Both quantities compare favorably with experiments.